Kajian Ekranisasi Novel Garis Waktu Karya Fiersa Besari dan Film Garis Waktu Yang Disutradarai Jeihan - Siti Wahidah; Dian Hartati (Peneliti.net, 2023)
The aim of this research is to present the process of equalization in the novel Garis Time by Fiersa Besari and the film Garis Time directed by Jeihan Angga. The method used is descriptive qualitative, namely by disclosing data according to existing research through words and sentences. The technique of collecting data is using techniques of reading, watching, taking notes, and comparing the two works. Research results: reduction in events, characters, and settings; added events, characters, settings, and times; variations in events, and characters. In addition, there is no change in the setting, either time or place. The changes that occur do not change the core of the story in the Garis Waktu novel. Precisely successful in attracting people, especially teenagers